Abstract 17409: Improved Diagnosis of Coronary Artery Disease Using Cardiac CT Compared With Exercise Stress Testing in an Urban Public Hospital Patient Population - Wu, Johnny; Rudenko, Ivan; Shekar, Chandana; Dahal, Suraj; Kinninger, April; Budoff, Matthew J; Roy, Sion (Circulation (New York, N.Y.), 2020)
IntroductionHeart disease remains the leading cause of death in the United States, with the disease burden particularly high in various racial and ethnic groups. In serving an underserved population comprised largely of Hispanic and African American individuals, it is crucial for an urban public hospital to diagnose heart disease in a resource-efficient and cost-effective manner. The greater positive predictive value of cardiac CT relative to exercise stress testing presents the opportunity for such hospitals to optimize resource utilization in identifying patients with coronary artery disease (CAD). HypothesisThe positive predictive value of cardiac CT in diagnosing CAD is greater than that of exercise stress testing in the patient population served by an urban public hospital. MethodsPatients at Harbor-UCLA Medical Center (Torrance, California) were identified for inclusion in this observational study on the basis of a positive (i.e., abnormal) exercise stress test result or a positive cardiac CT result, during the period between January 2015 and September 2019. These patients were subsequently referred for invasive coronary artery angiography, with the diagnosis of obstructive CAD established by an indication for revascularization via percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG). Data were analyzed using a two-tailed Z-test for two proportions. ResultsSeventy-six catheterization laboratory results were analyzed. Fifteen subjects with an abnormal exercise stress test result, out of a total of 41 (36.6%), had an indication for PCI or CABG. Twenty-five cardiac CT imaging subjects, out of a total of 35 (71.4%), had an indication for PCI or CABG. The proportion of positive cardiac CT results with an indication for PCI or CABG was significantly higher than the abnormal exercise stress test proportion (p=0.0024). ConclusionsAmong urban public hospital patients who were referred for invasive coronary artery angiography, it was determined that cardiac CT provides a greater positive predictive value in the diagnosis of obstructive CAD than exercise stress testing. This result may help guide the optimal allocation of diagnostic resources in an urban public hospital.